Direct and Indirect Costs of Diabetes in Brazil in 2016 - Paula Pereda; Vanessa Boarati; Bruna Guidetti; Ana Clara Duran (Ubiquity Press, 2022)
Background: The global economic burden ofDiabetes mellitus(DM) is expected to reach US$ 745 billion in 2030. The growing prevalence of the disease, mainly type 2 diabetes, is the result of population aging, nutritional transition, which include growing rates of obesity and consumption of foods high in sugar and fat. Brazil is the fourth country in the number of patients with diabetes globally and follows the global trends, with a continuous increase in prevalence. Objectives: To estimate the economic burden of DM in Brazil, including all direct and indirect costs. Methods: We used a cost-of-illness approach to calculate the total economic burden of DM. We used official healthcare-related statistics referring to 2016. Findings: We estimated the Brazilian economic burden to reach US$ 2.15 billion in 2016, of which 70.6% are indirect costs related to premature deaths, absenteeism, and early retirement. We estimate that if the rate of growth of diabetes prevalence remains in Brazil, direct and indirect costs of diabetes will more than double by 2030 (an increase of 133.4% or 6.2% per year). Conclusion: Our results are in accordance with the literature that shows that indirect costs are more relevant in low- and middle-income countries due to poorer access to health care, which result in higher mortality rates from non-communicable diseases. However, due to the potentially underestimated prevalence of diabetes in Brazil and the lack of access to nationwide private healthcare costs, we estimate costs of diabetes in Brazil to be higher than the conservative results we found. The onset of the COVID-19 pandemic is likely to result in even greater costs than what we estimated.